posted by Anonymous on .
So I am suppose to evaulate this problem y=tan^4(2x) and I am confused.
my friend did this : 3 tan ^4 (2x) d sec^ 2x (2x)= 6 tan ^4 (2x) d sec^2 (2x)
She says it's right but what confuses me is she deriving the 4 and made it a three? I did the problem like this:
tan^4 (2x)= 4 tan^3 (2x) d sec ^2 (2x)(2x)= 8 tan^3 (2x) d sec^2 (2x)
Can anyone explain this to me?
Go on :
wolframalpha dot com
Whe page be open in rectangle type :
then click option =
After few seconds when you see result click option :